Changes in income distributions and the role of tax-benefit policy during the great recession: An international perspective - Olivier Bargain; Tim Callan; Karina Doorley; Claire Keane (The Economic and Social Research Institute (ESRI), 2014)
This paper examines the impact on inequality and poverty of the economic crisis in four European countries, namely France, Germany, the UK and Ireland, and the contribution of tax and benefit policy changes. The period examined, 2008 to 2010, was one of great economic turmoil, yet it is unclear whether changes in inequality and poverty rates over this time period were mainly driven by changes in market income distributions or by tax- benefit policy reforms. We disentangle these effects by producing counterfactual ("no reform") scenarios using tax-benefit microsimulation and representative household surveys of each country. For the period under study, we find that the policy reaction has contributed to stabilizing or even decreasing inequality and relative poverty in the UK, France and especially in Ireland, a country where rising unemployment would have otherwise increased poverty. Market income inequality has nonetheless pushed up inequality and relative poverty in France. Relative poverty and, notably, child poverty, have increased in Germany due to policy responses combined with the increasing inequality of market income.
Keywords: H23; H53; I32; 330; Tax-benefit policy; Inequality; Poverty; Decomposition; Microsimulation; Crisis